ANALISIS PERLINDUNGAN HUKUM TERHADAP KONSUMEN DALAM JASA TITIP ONLINE KOSMETIK DAN PERAWATAN KULIT PADA MASA PANDEMI COVID-19 - Violeta Virgin G; Abustan (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2025)
This study aims to examine the construction of personal shopping services and the potential legal consequences faced by consumers of overseas online personal shopping services, such as counterfeit goods, delivery delays, and expired cosmetic products caused by delays or falsification. These issues may arise due to negligence and fraud by personal shoppers, which remain unavoidable to this day. Legally, online purchases may be delivered to a trusted individual or user of the online service. Consumer protection for entrusted service users in online transactions is based on Article 4 of Law No. 8 of 1999 on Consumer Protection. Protection for consumers against defective agreements and/or defective goods grants consumers the right to compensation if they declare that the quality or quantity of goods or services consumed does not match what was offered by the seller. Consumers also have the right to legal dispute resolution. Consumer protection in Islamic law is crucial as it concerns public interests and the relationship between humans and Allah. Islam views this protection as a duty of the state, both vertically (with Allah) and horizontally (with fellow humans), ensuring that goods circulating in the market comply with Islamic principles.